2022
DOI: 10.3390/pathogens11121507
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Over Pathogenic Bacteria Detected in Infected Tomatoes (Solanum lycopersicum L.) and Peppers (Capsicum annuum L.) in Bulgaria

Abstract: The ability of certain human pathogens to adapt to plants without losing their virulence toward people is a major concern today. Thus, the aim of the present work was the investigation of the presence of cross-over pathogenic bacteria in infected tomato and pepper plants. The objects of the study were 21 samples from seven different parts of the plants and three from tomato rhizosphere. In total, 26 strains were isolated, identified by MALDI-TOF, and phenotypically characterized. The PCR amplification of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 84 publications
1
8
0
Order By: Relevance
“…The strain GSE25 is a gram-negative bacterium and phenotypically challenging to distinguish from the family Enterobacteriaceae and other Pseudescherichia vulneris species based on 16S rRNA sequence similarity. It has been reported that P. vulneris was detected in several clinical isolates and had the potential to cause diarrheal illness by examining the genes for enterotoxins and exotoxin [ 19 , 20 , 21 ]. To ensure the availability and biosafety of GSE25 on crops, we tested the virulence factors and hemolysis of GSE25.…”
Section: Discussionmentioning
confidence: 99%
“…The strain GSE25 is a gram-negative bacterium and phenotypically challenging to distinguish from the family Enterobacteriaceae and other Pseudescherichia vulneris species based on 16S rRNA sequence similarity. It has been reported that P. vulneris was detected in several clinical isolates and had the potential to cause diarrheal illness by examining the genes for enterotoxins and exotoxin [ 19 , 20 , 21 ]. To ensure the availability and biosafety of GSE25 on crops, we tested the virulence factors and hemolysis of GSE25.…”
Section: Discussionmentioning
confidence: 99%
“…The isolates were identified by three different methods: PCR with genus-and speciesspecific primers [46,47], 16S rRNA sequencing [46], and MALDI-TOF (Matrix-Assisted Laser Desorption/Ionization Time-of-Flight) mass spectrometry [8]. Genus-and species-specific PCRs were performed in a total reaction volume of 25 µL containing 16.5 µL ultrapure H 2 O, 0.5 µL (5 pmol/µL) of each primer, 6.5 µL VWR Red Taq polymerase master Mix (VWR International bvba/sprl, Haasrode Researchpark Zone 3, Geldenaaksebaan 464 B-3001, Haasrode Belgium), and 1 µL extracted DNA.…”
Section: Species Identificationmentioning
confidence: 99%
“…This genus of bacteria forms a part of natural biomes of soil, water, sewage, and arable land, as well as populations in the gastrointestinal tracts (GITs) of mammals, birds, fishes, invertebrates, and insects [2][3][4][5][6]. Similarly, enterococci have been isolated from fresh vegetables (olive, pepper, celery, cilantro, mustard greens, spinach, collards, parsley, dill, cabbage, and cantaloupe) and wild plants also [7][8][9][10]. Flowering plants and crops have also been known to be carriers of enterococci [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations